Effects of Piper nigrum fruit and Cinnamum zeylanicum bark alcoholic extracts, alone and in combination, on scopolamine-induced memory impairment in mice - Mohammad Teymuori; Afsaneh Yegdaneh; Mohammad Rabbani (Wolters Kluwer Medknow Publications, 2021)
Background and purpose: Alzheimer's disease is a progressive brain disorder that is thought to be triggered via disruption of cholinergic neurons and enhanced oxidative stress. Therefore, antioxidant phytochemicals with the ability to fortify cholinergic function should help in preventing the progress of the disease. This study aimed at evaluating the combinational effects of two popular herbs one with anticholinesterase activity namely Piper nigrum and the other with antioxidant capacity, Cinnamomum zeylanicum. Experimental approach: In this study, P. nigrum extract (PN) (50, 100 mg/kg, ip) and C. zeylanicum extract (CZ) (100, 200, 400 mg/kg, ip) and their combinations were administered for 8 days before the injection of scopolamine (1 mg/kg, ip). Mice were then tested for their memory using two behavioral models, namely the object recognition test and the passive avoidance task. Findings/Results: Administration of scopolamine significantly impaired memory performance in both memory paradigms. In the passive avoidance test (PAT) model, PN at doses up to 100 mg/kg and CZ at doses up to 400 mg/kg did not significantly alter the memory impairment induced by scopolamine. The combination of these two plant extracts did not change the PAT parameters. In the object recognition test (ORT) model, however, administration of 100 mg/kg CZ alone and a combination of PN (50 mg/kg) with CZ (400 mg/kg), significantly increased the recognition index (P < 0.05). Conclusion and implications: Two plant extracts when administered alone or in combinations affected the memory performance differently in two memory paradigms. In the PAT model, the extracts did not show any memory improvement, in ORT, however, some improvements were observed after plant extracts.